Structural and Ionic Transport Properties of Protonic Conducting Solid Biopolymer Electrolytes Based on Carboxymethyl Cellulose Doped with Ammonium Fluoride - M. A. Ramlli; M. I. N. Isa (American Chemical Society Publications, 2024)
Fourier transform infrared (FT-IR), X-ray diffraction (XRD), and transference number measurement (TNM) techniques were applied to investigate the complexation, structural, and ionic transport properties of and the dominant charge-carrier species in a solid biopolymer electrolyte (SBE) system based on carboxymethyl cellulose (CMC) doped with ammonium fluoride (NH4F), which was prepared via a solution casting technique. The SBEs were partially opaque in appearance, with no phase separation. The presence of interactions between the host polymer (CMC) and the ionic dopant (NH4F) was proven by FT-IR analysis at the C?O band. XRD spectra analyzed using Origin 8 software disclose that the degree of crystallinity (?c%) of the SBEs decreased with the addition of NH4F, indicating an increase in the amorphous nature of the SBEs. Analysis of the ionic transport properties reveals that the ionic conductivity of the SBEs is dependent on the ionic mobility (?) and diffusion of ions (D). TNM analysis confirms that the SBEs are proton conductors.